FliS modulates FlgM activity by acting as a non‐canonical chaperone to control late flagellar gene expression, motility and biofilm formation in Yersinia pseudotuberculosis. (19th August 2013) - Xu, Shengjuan; Peng, Zhong; Cui, Boyu; Wang, Tietao; Song, Yunhong; Zhang, Lei; Wei, Gehong; Wang, Yao; Shen, Xihui
Summary The FlgM–FliA regulatory circuit plays a central role in coordinating bacterial flagellar assembly. In this study, we identified multiple novel binding partners of FlgM using bacterial two‐hybrid screening. Among these binding partners, FliS, the secretion chaperone of the filament protein FliC, was identified to compete with FliA for the binding of FlgM. We further showed that by binding to FlgM, FliS protects it from secretion and degradation, thus maintaining an intracellular pool of FlgM reserved as the FliS–FlgM complex. Consequently, we found that the flagellar late‐class promoter activities are significantly increased in the fliS deletion mutant. The fliS mutant is weakly motile and shows significantly increased biofilm formation on biotic surface. Based on the results obtained, we established for the first time the regulatory role of the flagellin chaperone FliS to fine‐tune late flagellar assembly by modulating FlgM activity.